A DC fault ride‐through and energy dissipation scheme for hybrid MMC‐MTDC integrating wind farms with overhead lines. Issue 18 (28th May 2019) - Cao, Shuai; Xiang, Wang; Lu, Xiaojun; Ling, Weixing; Wen, Jinyu
Abstract : To integrate bulk wind power, using modular multilevel converter (MMC) based DC grids is an effective solution to improve the flexibility and reliability of the power grid. This paper analyses a bipolar four‐terminal MMC based DC grid to integrate wind farms with overhead lines. Since the overhead lines are prone to DC faults, the hybrid MMC is adopted in the system to ride through DC faults. The fault ride‐through control strategies are designed, which remain continuous operation of wind turbines under DC faults. Besides, an adaptive dissipation control strategy associated with chopper resistances is designed to absorb surplus energy. Finally, simulations based on PSCAD/EMTDC platform verify the fault ride through control of hybrid MMC based DC grid and proves the effectiveness of the energy dissipation strategies.